INNOVATIVE MATERIALS AND ENGINEERING STRATEGIES IN U.S. CUSTOM VEHICLES - Maksymov, Oleksii (Global Prosperity, 2025)
Abstract. The article is devoted to the analysis of innovative materials and engineering strategies used in the manufacture of customized cars in the USA. Scientific novelty is a comprehensive approach to the design and manufacture of new generation composite components using the precision fiberglass innovation (PFIS) technology. The purpose of the study is to identify modern innovative technologies for the production of fiberglass and fiberglass that have practical application in the automotive industry. During the scientific study, general scientific methods of cognition were used: analysis, synthesis, comparison, systematization, generalization, modeling. The results of the study show that none of the existing industrial technologies for the formation of fiberglass is universal for all types of automotive components. Special attention is paid to the author’s PFIS system, which is fundamentally different from classical approaches in that it provides full integration of the design and production stages. Within the framework of PFIS, controlled fiber orientation according to load distribution, adaptive change in part thickness, and rapid change of structures without loss of production efficiency are implemented. The proposed system allows creating complex geometric shapes taking into account local requirements for mechanical properties, which is critically important for engineering solutions in the field of custom automotive manufacturing, electric vehicles, and the defense and aerospace industries. It is shown that thanks to PFIS, it becomes possible to implement high-precision optimization of mass-dimensional characteristics of parts, reduce material consumption, and ensure strategic production efficiency factors: competitiveness, stability of innovations, adaptability to new market challenges. The practical significance of the research lies in the implementation of a flexible high-tech platform for the manufacture of innovative composite parts in modern automotive manufacturing.